Argumentation in Complex Communication: Managing Disagreement in a Polylogue by Marcin Lewiński and Mark Aakhus - Aikin, Scott; Grosu, Alice (Informal Logic, 2025)
This article reviews Marcin Lewinski and Mark Aakhus’s Argumentation in Complex Communication (Oxford 2022).